Does race matter? An examination of defendant race on legal decision making in the context of actuarial violence risk assessments - Davis, Riley M. (Legal and criminological psychology, 2022)
Purpose There is no doubt that racial biases contribute to the overrepresentation of people of colour in the justice system. Specialized violence risk tools are meant to increase the objectivity with which certain legal decisions are made. However, the degree to which racial biases influence risk-related decisions remains unclear despite the use of these tools. Methods This study examined whether a hypothetical defendant's race would influence the risk-related perceptions and decisions of 280 jury-eligible participants in the United States when presented with expert opinions concerning the defendant's likelihood of future violence. Participants were randomly assigned to one of three conditions that varied the identified race of the defendant (i.e., Black, White, or not reported). Results Participants reported their perceptions about the defendant's likelihood of violence, desired social distance from the defendant, and the severity of punishment they would recommend. Contrary to hypotheses, there were no statistically significant effects of defendant race on risk decisions, suggesting that expert testimony may have mitigated the influence of race. However participants higher in explicit racial bias were more likely to perceive a Black defendant as higher risk; no association between racial attitudes and risk perception emerged in the other defendant conditions. Conclusions Limitations and future directions for research, including methods for increasing external validity, assessing impression management, and diversifying demographics, are discussed. In the current socio-political climate, it is imperative that forensic psychological research continue to explore the ways in which racial biases may lead to inequitable psycho-legal decisions.